2020
DOI: 10.1016/j.heliyon.2020.e04694
|View full text |Cite
|
Sign up to set email alerts
|

Character strengths and sustainable technology adoption by smallholder farmers

Abstract: Sustainable food systems are required to feed a growing world population. Smallholder farmers, who produce a significant share of the food supply in many developing countries, can play a crucial role in applying such systems. In agriculture, various innovative technologies promise to have a significant part in securing a sustainable future. Clearly, however, before new technologies can benefit their users, they must first be adopted. Why do most smallholders avoid using modern cultivation technologies? Rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 50 publications
2
5
1
Order By: Relevance
“…This implies that highly educated, less educated and uneducated farmers can be either innovative or less innovative. Contrary to this result, research by (Ruzzante et al, 2021;Bukchin and Kerret, 2020;Ntshangase et al, 2018) found farmer education to significantly influencing their innovativeness. The present finding does not downplay the importance of formal education in innovation adoption; however, it opens a debate that other factors also influence farmers' innovation decisions, and for that matter, education alone cannot be used as a basis to conclude that one farmer is more innovative than the other.…”
Section: Analysis Of Adopter Categories and Socioeconomic Indicatorscontrasting
confidence: 63%
See 1 more Smart Citation
“…This implies that highly educated, less educated and uneducated farmers can be either innovative or less innovative. Contrary to this result, research by (Ruzzante et al, 2021;Bukchin and Kerret, 2020;Ntshangase et al, 2018) found farmer education to significantly influencing their innovativeness. The present finding does not downplay the importance of formal education in innovation adoption; however, it opens a debate that other factors also influence farmers' innovation decisions, and for that matter, education alone cannot be used as a basis to conclude that one farmer is more innovative than the other.…”
Section: Analysis Of Adopter Categories and Socioeconomic Indicatorscontrasting
confidence: 63%
“…A study by Diiro and Sam (2015) found that farmers in Uganda who earned higher income and had more assets applied new technologies (seed varieties) on their farms more than farmers whose incomes were lower. Similarly, Bukchin and Kerret (2020) found that higher annual income increased farmers' drip irrigation adoption. The finding from this study, therefore, adds to the academic debate that higher annual income of farmers directly increases their innovativeness; hence, our results in Table 3 , showing a higher number of smallholder farmers with lower annual income, could explain why many smallholder farmers are less innovative (see Table 4 and Figure 2 ).…”
Section: Resultsmentioning
confidence: 96%
“…Poisson is a process of satisfying the assumptions of the probability distribution of the number of occurrences of the event in a fixed time interval [33]. Studies by Ojo et al [29] and Bukchin et al [34] have stated that farmers usually weigh the technology's benefits before adopting it. The study used the PRM because diagnostic tests revealed the absence of overdispersion and under dispersion.…”
Section: The Intensity Of Csa Use Among Smallholder Maize Farmersmentioning
confidence: 99%
“…Li et al [23] argued that, this was partly due to the lack of motivation of farmers. Thus the approach needed relating to the adoption of sustainable technology is an extension based on the strength of the character of farmers [24]. From an economic aspect, several indicators must be met for a technology to be adopted sustainably.…”
Section: Determination Of Standard Fertilization In Agronomy Effectiveness Based Researchmentioning
confidence: 99%